Effectiveness of practice guidelines nutritional care and basic nutritional care on anthropometric and metabolic outcomes in type 2 diabetes mellitus patients at Sultan Qaboos University Hospital, Oman - Al-Shookri, Ali Obaid Salim (2013)
Diabetes is a common problem worldwide. Oman is facing increased incidence of type 2 diabetes. The prevalence of type 2 diabetes in Oman was 10 – 14% in 2007 and the figure is expected to rise to 14-20% by the year 2025. There is thus a critical need to improve the nutritional care for the increasing cases of type 2 diabetes patients in Oman. The main objective of this randomized clinical trial is to investigate the effectiveness of the practice guideline nutritional care (PGC) compared to the basic nutrition care (BC) on anthropometric and clinical outcomes in adults with type 2 diabetes in the Sultan Qaboos University Hospital in the Sultanate of Oman. The sample size required for the study was computed using G*Power 3.1.3 for repeated measures ANOVA, to detect an effect size of 0.24, significance level at 0.05, 95% power, giving a total sample size of 156 for two groups, or about 78 per group. Assuming a 25% dropout rate, the final sample size was increased to 200 subjects, with 100 subjects in each intervention group. Patients were randomly assigned to either the PGC or BC group. Out of 200 participants who enrolled for the study, 170 men and women aged 30 to70 years met the inclusion and exclusion criteria. This represents 85% of the 200 subjects enrolled. Out of these, 85 were assigned randomly to the BC group and 85 to the PGC group. In the BC group, patients had only one appointment with the dietitian during which nutritional goals designed to improve glycemic control were introduced and general principles of nutrition management were discussed with nutritional prescription and education. The PGC group patients had three appointments with a dietitian with specific assessments and intervention measures according to the practice guidelines of medical nutritional treatment developed by American Dietetic Association. Anthropometric (weight, height, BMI and waist circumference), biochemical (fasting blood glucose, HbA1c, triglycerides, cholesterol, LDL cholesterol and HDL cholesterol), dietary intake (total energy, carbohydrate, fat, cholesterol, saturated fatty acids, monounsaturated fatty acids and polyunsaturated fatty acids) and physical activity (total physical activity MET-minutes/week, walking MET-minutes/week,moderate MET-minutes/week and vigorous MET-minutes/week) variables were measured at three time points (0, 3, 6 months). The comparison between groups over the study period of 6 months was quantified using Multivariate General Linear Modeling Repeated Measures ANOVA (GLMANOVA).Normality was checked for variables using the Kolmogorov-Smirnov test,and equality of variances using Levene’s test. Body weight, BMI, HbA1c,FPG and triglycerides values of PGC group at 3 months and 6 months were significantly lower than values at time entry, with no significant change in levels of cholesterol, LDL cholesterol and HDL cholesterol over the study period. There is no significant change in anthropometric or glycemic outcomes in BC group over the entire period of study. BC group values of cholesterol at 3 months and HDL cholesterol at 6 months were significantly lower compared to values at time of entry. At the end of 3 months, the PGC group’s mean value of FPG was significantly lower than that of the BC group. The PGC group’s mean values for waist circumference, HbA1c, cholesterol, LDL cholesterol and triglycerides were also significantly lower than those values for the BC group at the end of 6 months of the study. The mean values for the dietary intake of total energy, carbohydrate, protein, fat,cholesterol, saturated fatty acids and polyunsaturated fatty acids in the PGC group reduced significantly during the first 3 months compared to the beginning of the study. The significant reduction continued during the following 3 months for the intake of carbohydrate, protein, fat and cholesterol. However, there were no significant changes shown in the mean values for the intake of total energy, saturated fatty acids and polyunsaturated fatty acids at 6 months compared to values at 3 months within the PGC group. The dietary intake mean values of total energy, carbohydrate, fat, cholesterol,saturated fatty acids and polyunsaturated fatty acids of the PGC group at 3 months and 6 months were significantly lower than the corresponding mean values of the BC group at the same periods of study. At 6 months of the study, the PGC group showed significantly lower saturated fatty acids intake than that of the BC group. It was found that total physical activity MET-minutes/week of the PGC group increased significantly during the first 3 months. The same was found for walking MET-minutes/week, moderate MET-minutes/week and vigorous MET-minutes/week values. At 6 months, total physical activity, walking and vigorous METminutes/week values did not show significant differences compared to the values at 3 months. The PGC mean values for MET-minutes/week of total, walking, moderate and vigorous physical activity at 3 months and 6 months were significantly higher than the values of the BC group at the same study periods. The Practice Guideline Nutrition therapy provided by dietitians to patients with type 2 diabetes did not show significant improvements in anthropometric (weight and BMI) outcomes over the period of the study compared to patients who received Basic Nutritional Care. In summary, the glycemic control and lipid profile outcomes improved significantly with the application of the Practice Guideline Nutrition therapy compared to the Basic Nutritional Care. The patients’ average HbA1c, triglycerides, cholesterol, LDL cholesterol values at the end of the study period were significantly lower in the PGC group than for the BC group. The significant improvement in HbA1c and lipid profile of the PGC group was accompanied by significant increase in the physical activity levels and improved dietary intake. As a result, we conclude that the metabolic outcomes of type 2 diabetes subjects improved with the Practice Guidelines Nutritional care compared to the Basic Nutritional Care, and that more intensive and longer duration medical nutrition therapy are needed for better anthropometric outcomes.